Samoregulacja emocji a poczucie własnej skuteczności pielęgniarek w opiece nad innymi = Emotional self-regulation and self-efficacy among nurses in the context of caring for others - Wojciechowska, Ludwika; Berezecka, Zuzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nursing is a profession that requires not only knowledge and practical skills but also specific psychological competencies. Among the competencies that support nurses in providing patient care are emotional intelligence and self-efficacy, as effective coping with professional challenges and building satisfying relationships with patients largely depend on them. The aim of the study was to analyze the relationship between the emotional intelligence dimension of emotion self-regulation and self-efficacy in a professional group of nurses.
Keywords: samoregulacja emocji; poczucie własnej skuteczności; kompetencje emocjonalne; pielęgniarki; emotional self-regulation; self-efficacy; emotional competencies; nurse